Cell volume measurement using scanning ion conductance microscopy. - Korchev, Y E (2000)
We report a novel scanning ion conductance microscopy (SICM) technique for assessing the volume of living cells, which allows quantitative, high-resolution characterization of dynamic changes in cell volume while retaining the cell functionality. The technique can measure a wide range of volumes from 10(-19) to 10(-9) liter. The cell volume, as well as the volume of small cellular structures such as lamelopodia, dendrites, processes, or microvilli, can be measured with the 2.5 x 10(-20) liter resolution. The sample does not require any preliminary preparation before cell volume measurement. Both cell volume and surface characteristics can be simultaneously and continuously assessed during relatively long experiments. The SICM method can also be used for rapid estimation of the changes in cell volume. These are important when monitoring the cell responses to different physiological stimuli.